2015
DOI: 10.1002/rcs.1662
|View full text |Cite
|
Sign up to set email alerts
|

Robotic sleeve gastrectomy for morbid obesity: report of a 5 year experience

Abstract: Robotic sleeve gastrectomy is an effective procedure as far as initial excess weight loss is concerned and this loss is well maintained 5 years post-operatively, a finding similar to relevant data after conventional laparoscopic sleeve gastrectomy. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…24 The laparoscopic nature of SG allows for faster healing and recovery time with early mobilization and relatively less pain and scarring. 25,26 A review study conducted by Diamantis et al 24 found that SG procedures not only resulted in immediate and midterm weight loss, but also that this weight loss was maintained, on average, at >50 per cent of the original weight even after five years.…”
Section: No 2 Weight Loss and Glycemic Controlmentioning
confidence: 99%
“…24 The laparoscopic nature of SG allows for faster healing and recovery time with early mobilization and relatively less pain and scarring. 25,26 A review study conducted by Diamantis et al 24 found that SG procedures not only resulted in immediate and midterm weight loss, but also that this weight loss was maintained, on average, at >50 per cent of the original weight even after five years.…”
Section: No 2 Weight Loss and Glycemic Controlmentioning
confidence: 99%
“…Robot-assisted surgery brings the benefits of minimally invasive surgery to the weight-loss surgery [ 8 ]. The da Vinci operating robot was approved by FDA in 2000, and currently is widely applied in bariatric surgery [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Metabolic and Bariatric Surgery Accreditation and Quality Improvement Program (MBSAQIP) database showed that, in the last few years, the da Vinci robotic platform has increasingly emerged as an attractive technology in bariatric surgery [ 8 , 9 ]. At present, da Vinci sleeve gastrectomy has been carried out, showing good results [ 10 , 11 ]. Robotic-assisted sleeve gastrectomy offers a viable platform to surgeons performing sleeve gastrectomy.…”
Section: Introductionmentioning
confidence: 99%